A critical study of the identification of the place in Sri Lanka where the Tripitaka was committed to writing - Banda, G.R.G. (Research Symposium 2009 - Faculty of Graduate Studies, University of Kelaniya, 2009)
Though there are canonical and non canonical texts of ancient Buddhism in some languages, it is only in the Pali language that we have a complete Tripitaka which belongs to the Theravada. Hence in respect of history of Buddhism it is very important for the Buddhist world, the Orient and the Occident, to identify the sacred place where this short term greatest book writing project of the world implemented in the reign of Valagamba in Sri Lanka. (1st century B.C.) Many Sri Lankans and foreigners who are not well versed in ancient sources, traditionally believe that this event occurred at Aluvihara near Matale. Our greatest historian and archaeologist, Prof. Paranavitana who was well versed in earlier sources had written in the “University History of Ceylon (p. 172) that earlier sources do not connect Aluvihare with this event. Historical writings refer Alulena in Dakkhina Malaya (South / South west hills) as the place connected to this event. Some present historians (in Sabaragamuwa Vamsa Kata) state that Matula Alulena view is more acceptable than Aluvihare view. Hence controversial issue has arisen. I attempt in my research with about 30 evidences to prove that the place mentioned in earlier sources is Alulena in Matula (Attanagoda) near Kegalle and not Aluvihare in Uttara Malaya (north hill country) As matters are such, state affiliated institutions like universities ministries of education, cultural affairs, Buddhist affairs, NIE, tourist board, archaeology dept. are seemed lethargic to find a solution to this dilemma which affect the whole Buddhist world. So a recognized research thesis written in an international language (English) is felt essential to awaken the eyes of the Sri Lankan state and the World Buddhist Association to do a fair justice to Alulena, the source of Buddhist literature and result in change of misconceptions around Aluvihare.